Pengaruh Pelatihan Kerja Dan Penilaian Kinerja Terhadap Produktivitas Kerja Pegawai PT Airkon Pratama: The Effect of On-the-Job Training and Performance Appraisals on Employee Productivity at PT Airkon Pratama - Asep Saepul Hidayat; Ratih Hastasari (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
- In the era of globalization, business competition is becoming increasingly intense, and companies must enhance the work productivity of their employees to stay competitive. This research aims to examine the effect of job training and performance appraisal on the work productivity of PT Airkon Pratama employees. The study utilizes an associative descriptive quantitative method. The respondents included 131 employees working at the PT Airkon Pratama office in Bekasi City. The data sources consisted of primary data obtained through observation and questionnaire distribution, while secondary data was collected through literature studies. The data were analyzed using SPSS version 25. The results revealed a positive and significant impact of job training on work productivity. Similarly, performance appraisal was found to have a positive and significant effect on work productivity. The F test also demonstrated that job training and performance appraisal together have a significant influence on work productivity.